Torque loss in a gearbox lubricated with wind turbine gear oils. (18th February 2013) - Gonçalves, David E. P.; Fernandes, Carlos M. C. G.; Martins, Ramiro C.; Seabra, Jorge H. O.
ABSTRACT: In this study, four different fully formulated ISO VG 320 wind turbine gear oils were select: a mineral oil‐based, a polyalphaolefin‐based, an ester‐based and a polyalkyleneglycol‐based fluids. Their physical properties (viscosity, thermoviscosity, piezoviscosity etc.) were characterised for a wide range of operating temperatures. A two‐stage multiplying gearbox, with helical gears, was selected to evaluate the influence of the wind turbine gear oil formulation on torque loss with the gearbox operating at low speed (130–230 rpm) and high torque (500–1000 Nm). The results obtained showed that each wind turbine gear oil formulation generated very different torque losses, evacuated heat flows and operating temperatures, with differences above 20 °C under the most severe operating conditions. A numerical model was developed, simulating all power loss mechanisms inside the gearbox, in particular the churning and friction losses. The coefficients of friction, between gear teeth and between rolling elements and bearing raceways, were calculated for all the tested oils. Copyright © 2013 John Wiley & Sons, Ltd.